O Ceará enferrujado: a ferrovia e os trilhos da modernização do território - Alencar, Igor Carlos Feitosa (2021)
The Brazilian railway issue is a considerably debated topic, mainly from the perspective of historiographical studies of communication networks, which dates back to the end of the 19th century, a period of great political-economic-spatial transformations. Investigating the particularities of these processes at the provincial scale allows us to apprehend the local conditions imprinted on them. Therefore, this research aims to understand the installation of the Baturité Railroad between 1872 and 1926, from Fortaleza to the city of Crato, as the central element of a process of territorial modernization. The methodology combines description with critical analysis, which seeks to unravel the contradictions of the process, more specifically, of form and content. It began with a bibliographic survey guided by major themes - the “railway issue”, “socio-spatial training” and “modernity and territorial modernization”. The investigation was based mainly on documentary sources, especially official ones (Report of Presidents of the Province; Messages, Notices, Decrees and Laws); also in news and journalistic reports; in addition to other sources, such as census data. Initially, an attempt was made to apprehend the global and national context circumscribed to the Second Brazilian Reign, when the railway projects represented part of a process of capitalist expansion, led by England, which gave dependent economies the need for territorial adjustments. When analyzing this process in Ceará, we can verify that installing the railroad was an initiative of political elite - initially consolidating the transformation of the agro-export productive base of the province and aiming at advancing over the sertão and what was produced in it. In this context, in addition to the aspects that ensured the start of construction, it was investigated how it was ensured, for more than five decades, that the project was fully installed up to Crato, the city of Boca de Sertão located in the extreme south of the province of Ceará. The analysis of the documents and data collected show the essentiality of employing hand labor of drought migrants to advance the works. The result of the process of territorial modernization in Ceará took place on two fronts: labor relations were socially transformed with the incorporation of the sertanejos in the railway works, implying a forced process of proletarianization; and, in addition, territorialized the desires of the commercial bourgeoisie with the implementation of the tracks, changing the flow conditions and shaping an urban network from the expansion of the frontier of accumulation in the hinterland.